Avaliação da atratividade de espaços públicos requalificados para o lazer aplicada a uma cidade de médio porte - Fabiani, Denize (2018)
The public spaces for leisure are responsible for meeting the demands of recreation, sports practices, contact with the environment and other activities that contemplate collective wellbeing, as well as reducing environmental and social problems. For this reason, there is a need for intervention and requalification of existing areas, which for various reasons became empty, abandoned and underutilized during the urban process, yet possessing great potential for reuse and reintegration into the city. Recently, several public spaces were reclassified in the city of Passo Fundo / RS, highlighting the city's only urban park, in the central region, and the other two new spaces denominated by the municipalities of parks, that until then, consisted of an area of permanent preservation despised in the urban network and of a set of central beds of an avenue present in a sectorial neighborhood. In this perspective, the objective of this study was to investigate and evaluate the potential attractions for the appropriation of public spaces requalified for leisure in the city under study and theirinfluence on the perception of users. By means of case studies, the spaces were characterized and analyzed technically regarding the physical, formal, functional and perceptive aspects, from a post-occupation evaluation, with application of questionnaires to users and behavioral observations. Based on the comparison between the parks and the attractiveness of the parks, the obtained data allowed to know the potentially attractive aspects; to determine, through correlation, their influence on the form of appropriation, intensity of use and levels of satisfaction; and establish guidelines for future interventions in public spaces. The results showed that one of the analyzed leisure public spaces has more attractive attributes for use and appropriation, greater intensity of use and better levels of satisfaction. However, attractiveness and satisfaction with the public space, regardless of physical, formal and functional qualification, as well as intensity of use, are perceived differently by users, since they are related to the needs and characteristics of each individual, not affecting the importance given to the site. Therefore, the three parks analyzed brought about, through their requalification, urban modifications through a positive strategic planning, making previously unused public spaces by the population, potentially and concretely attractive.